Effects of Metformin in Patients with Poorly Controlled, Insulin-Treated Type 2 Diabetes Mellitus - Altayari, Abid A.; Alrehaili, Khalid Faraj; Alharbi, Sanad Abdulrahman; Kaabi, Yahya Ali; Altamimi, Abdullah Khaled; Alzahrani, Yousra Khudran; Albalawi, Sabrin Saleh; Alzeriry, Abdulrahman Soliman; Alruwaythi, Abdullah Abdulrahman Saleh; Yahya M, Althubyani, Mohammed; Al Malki, Mohammed Al Hassan; Almotairi, Omar Owaydhah Salem; et al. (Journal of Ecohumanism, 2024)
Background: Metformin is an oral anti-diabetic drug widely recognized as the first-line therapy in the treatment of Type 2 Diabetes Mellitus (T2DM) Aim: To assess the impact of metformin on glycemic control, insulin dosage, and side effects in poorly controlled, insulin-treated type 2 diabetes patients. Patients and methods: A comprehensive literature search was conducted using electronic databases such as PubMed, Embase, Cochrane Library, and Web of Science. The search terms included "metformin," "insulin," "type 2 diabetes," "poorly controlled," and "randomized controlled trial." The search was limited to studies published in English up to December 2022. Results: The study analyzed three studies on total cholesterol levels at follow-up, LDL follow-up, HDL at follow-up, and triglycerides at follow-up. A non-significant heterogeneity was detected, resulting in a non-significant difference between groups. A random-effect model was used for analysis, revealing a combined mean difference of -0.11 and 95% CIs of -2.66. The combined results showed no statistically significant difference between groups regarding LDL baseline (Z = 1.73, P = 0.08), HDL at follow-up (Z = 1.87, P = 0.06), and triglycerides (Z = 1.04, P=0.30). A highly significant heterogeneity was detected in the Side Effect (Two studies reported), demonstrating a highly statistically significant difference between groups regarding this effect (Z = 7.01, P ˂0.001). The results suggest that a combination of factors may influence cholesterol levels and triglycerides at follow-up. Conclusion: Metformin significantly improves diabetes duration, insulin therapy duration, and glycated hemoglobin levels in Type 2 diabetes patients, with moderate side effects risk. Further studies are needed for long-term safety.